1990
DOI: 10.1021/ma00212a008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation and mass-spectrometric fragmentation processes of polyesters studied by time/temperature-resolved pyrolysis-field ionization mass spectrometry

Abstract: Linear polyesters of the lactone and the diol-dicarboxylic acid types have been pyrolyzed in the ion source of a mass spectrometer. The gaseous degradation products were softly ionized by means of field ionization. Oligomers were the dominant products observed as protonated species. In contrast to the general experience with soft ionization mass spectrometry, with polyesters distinct mass spectrometric fragmentation occurs forming singly charged and doubly charged carboxonium and hydroxonium ions, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…In a study of degradation of aliphatic polyesters, the anomalous behavior of PPAd was explained through formation of specific degradation products. These are butyrodiketene, cyclopentanone, and a stable cyclic anhydride with seven‐membered ring 31. Thus, PPAd represents a unique case of aliphatic polyester, the degradation of which results in formation of favorable stable products.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of degradation of aliphatic polyesters, the anomalous behavior of PPAd was explained through formation of specific degradation products. These are butyrodiketene, cyclopentanone, and a stable cyclic anhydride with seven‐membered ring 31. Thus, PPAd represents a unique case of aliphatic polyester, the degradation of which results in formation of favorable stable products.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Studies on the thermal stability of PLLA have been reported by several groups. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Based on the reported results, thermal degradation of PLLA is more complex than the simple reaction that gives lactide, and significant amounts of the other volatile decomposition products are also created during pyrolysis.…”
Section: Thermal Degradation Processes Of Poly(lactide)mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Iwabuchi et al 8 investigated the thermal degradation behavior under isothermal degradation condition at 220°C. By monitoring the time-dependent changes in sample weight and viscosity, they proposed a single step degradation mechanism, where the polymer degrades by specific removal of cyclic monomer from the end groups.…”
Section: Introductionmentioning
confidence: 99%